Beyond the Strike Statistics - Finn, Ed (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1973)
Before examining many of the myths surrounding the strike phenomenon, the author of this paper feels that the accuracy of the strike figures themselves should be questionned.